Death on the Nile [videorecording (DVD)] - Branagh, Kenneth; Green, Michael (Screenwriter); Bateman, Tom, 1989-; Bening, Annette; Brand, Russell, 1975-; Fazal, Ali, 1986-; French, Dawn; Gadot, Gal, 1985-; Hammer, Armie, 1986-; Leslie, Rose, 1987-; Mackey, Emma, 1996-; Okonedo, Sophie; et al. (20th Century Studios, 2022)
Belgian sleuth Hercule Poirot's Egyptian vacation aboard a glamorous river steamer turns into a terrifying search for a murderer when a picture-perfect couple's idyllic honeymoon is tragically cut short. Set against an epic landscape of sweeping desert vistas and the majestic Giza pyramids, this tale of unbridled passion and incapacitating jealousy features a cosmopolitan group of impeccably dressed travelers, and enough wicked twists and turns to leave audiences guessing until the final, shocking denouement.